Early failures when using three different adhesively retained core build-up materials: a randomized controlled trial - Zenthöfer, Andreas; Lorenzo Bermejo, Justo; Bömicke, Wolfgang; Frese, Cornelia; Özcan, Rumeysa; Rammelsberg, Peter; Ohlmann, Brigitte (Clinical oral investigations, 2022)
To compare the failure rates for three different adhesively retained core build-up composites up to the incorporation of a permanent fixed dental prosthesis (FDP), and to identify potential failure risk factors.
Online veröffentlicht: 7. September 2021
Gesehen am 02.11.2023